SANTRIPRENEUR: Program Peningkatan Kemampuan Berwirausaha Santri Pondok Pesantren melalu Pelatihan Sablon Digital - Muhammad Hasyim Ibnu Abbas; Hadi Sumarsono; Yogi Dwi Satrio; Magistyo Purboyo Priambodo (Martabe : Jurnal Pengabdian Kepada Masyarakat, 2019)
Pengabdian Kepada Masyarakat is a program with a mission to implement the development of science and technology from tertiary institutions to the community to support and improve the welfare of the community. In this entrepreneurship development program, the team conducted production training in the creative industry sector in the form of screen printing expertise at Anwarul Huda Islamic Boarding School in Malang. The students are deemed necessary to be given assistance to increase economic independence. In addition, this is also supported by Anwarul Huda Islamic Boarding School in Malang which allows students to become entrepreneurs to create economically independent students. Through this community service program which will be carried out by Lecturers from the UM Research and Community Service Institute (LP2M), in collaboration with practitioners in the field of creative industries, new entrepreneurs and students in the field of creative industries are expected to be born, and can manage businesses better. This activity is divided into four stages namely observation of partner needs analysis, Socialization, Training, and Assistance.